2017
DOI: 10.9775/kvfd.2017.17504
|View full text |Cite
|
Sign up to set email alerts
|

Kısa (Chihuahua köpek) ve Uzun (Asya fili) Ömürlü Hayvanlarda Artan Yaş İle Birlikte Telomerik Yıpranma

Abstract: Citation of This Article AbstractHere, we explored the rate of telomere attrition with increasing age by real-time quantitative PCR (qPCR) in a short-(Chihuahua dog) and long-(Asian elephant) lived species. A total of 122 Asian elephants (female = 106, male = 16) ranging from 24-840 months of age, and 89 Chihuahuas (female = 65, male = 24) 1-179 months of age were used in this study. We found that young (pre-and peri-pubertal) Asian elephants had a higher relative telomere length (RTL) compared to dogs. A low,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…(i.4) Elephants (order Proboscidea, suborder Elephantiformes). Telomere length has been studied in relation to age in the Asian elephant using 122 samples across the full lifespan of the species (Buddhachat et al, 2017). A significant decline in telomere length was found (P < 0.05) independent of any observed effect for sex-linked differences in ageing rate.…”
Section: Speciesmentioning
confidence: 99%
“…(i.4) Elephants (order Proboscidea, suborder Elephantiformes). Telomere length has been studied in relation to age in the Asian elephant using 122 samples across the full lifespan of the species (Buddhachat et al, 2017). A significant decline in telomere length was found (P < 0.05) independent of any observed effect for sex-linked differences in ageing rate.…”
Section: Speciesmentioning
confidence: 99%
“…They play an important role in maintaining chromosome integrity which may be affected by deterioration or damage (Blackburn, 1991;Shay and Wright, 2000;Takasaki et al, 2003) Telomere length shortening occurs normally in most somatic cells during DNA replication throughout the lifespan of living organisms (McEachern et al, 2000;Cawthon, 2002;McKevitt et al, 2002;Haussmann et al, 2003;Vleck et al, 2003;Callicott and Womack, 2006;Hewakapuge et al, 2008;Izzo et al, 2011). Presently, telomere length has been widely used to estimate age in human subjects (Hewakapuge et al, 2008;Karlsson et al, 2008) and for several other mammalian species such as mice (Callicott andWomack, 2006), dogs (Nasir et al, 2001;McKevitt et al, 2002;Fick et al, 2012;Buddhachat et al, 2017), sea lions (Izzo et al, 2011) and elephants (Buddhachat et al, 2017). However, when the outcomes from several studies were compared, a degree of inconsistency was observed among the various subjects.…”
Section: Introductionmentioning
confidence: 99%